2013
DOI: 10.1080/1745039x.2013.776329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fat sources in parental diets on growth performance, villus morphology, digestive enzymes and colorectal microbiota in pigeon squabs

Abstract: The influence of different fat sources in pigeon diets on performance, gut morphology, digestive enzymes and colorectal microbiota of their squabs was investigated from hatching to 28 days of age. Parent White King pigeons (240 males and 240 females) were randomly assigned to four dietary treatments, each including six replications of 10 pairs (one pair per cage). Four hundred eighty newly hatched squabs were randomly allocated, and two squabs were raised by a pair of parent pigeons. Pigeons were fed a basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The crypt depth of the duodenum and jejunum was greater (P <0.05) in birds fed LO than in other treatments in both the starter and finisher phases. The lower villi height in LO birds supported the findings of Xie et al (2013), who reported that supplementing oil rich with n-3 polyunsaturated fatty acids (PUFA) in diet of squabs caused a lower bodyweight gain and affected villus morphology compared with lard, palm oil and soybean oil. Oils containing high proportions of readily oxidizable n-3 PUFA could lower the oxidative stability of gut, which could predispose cell or tissue to free radical attack.…”
Section: Resultssupporting
confidence: 78%
“…The crypt depth of the duodenum and jejunum was greater (P <0.05) in birds fed LO than in other treatments in both the starter and finisher phases. The lower villi height in LO birds supported the findings of Xie et al (2013), who reported that supplementing oil rich with n-3 polyunsaturated fatty acids (PUFA) in diet of squabs caused a lower bodyweight gain and affected villus morphology compared with lard, palm oil and soybean oil. Oils containing high proportions of readily oxidizable n-3 PUFA could lower the oxidative stability of gut, which could predispose cell or tissue to free radical attack.…”
Section: Resultssupporting
confidence: 78%
“…Treatment 3 which had the best conversion ratio included only 3% soybean oil. This is related to the effect of fat on feed intake which causes fixed energy absorption of the bird by lower feed intake [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Research on animals was conducted in Rudsar, Iran (37.1378° N, 50.2836° E) and all the procedures used were approved by the Ethics Committee in Animal Use (Approval date: 10/05/2016; No: 10038). The experiment, in a completely randomized design with 6 treatments and 4 replicates using 240 1-day-old male chicks of strain Ross 308, was conducted in the starter period (1-10 day), grower period (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and finisher period (29-42). Each replication included 10 chicks.…”
Section: Chickens Diets and Managementmentioning
confidence: 99%
“…The ingredients, nutrient levels and analyzed LA content of experimental diets for parent pigeons were shown in Table 1. The fatty acid composition of each diet analyzed according to Xie et al [18] were shown in Additional le 1. The pigeons were given to water ad libitum and were fed twice daily (7:00 a.m. and 3:00 p.m.) throughout the experiment.…”
Section: Birds and Conditionsmentioning
confidence: 99%